How to prevent loss of essential vitamins during food processing (Research, Society and Development, 2022)
Vitamin micronutrients are paramount to the human body. Water-soluble vitamins are classified as B-complex vitamins (B1, B2, B3, B6, B9, B12) and Vitamin C. The lack of these vitamins can lead to diseases that harm human health, such as pernicious anemia and pellagra. During the heat treatment these vitamins end up being lost. Due to the Covid-19 Pandemic, Brazilian industries increased the export of vitamin C rich fruits like orange and lemon by 132 % and 12 % respectively. With the help of researchers, industries have the potential to develop adequate supplements to provide the energy needed by the human body. Thus, we aimed to survey papers reporting on the losses of vitamin B and C during processing. It is noticed that several foods have antioxidant properties due to the presence of vitamin nutrients, being essential for the body, because its function prevents cellular oxidation and favors the defense against free radicals. Among the food processing methods, microencapsulation and lyophilization are very effective in preserving the bioactive components of vitamins.